A Randomized Trial of Combined Citalopram and Naltrexone for Nonabstinent Outpatients With Co-Occurring Alcohol Dependence and Major Depression. Issue 2 (April 2015) - Adamson, Simon J.; Sellman, J. Douglas; Foulds, James A.; Frampton, Christopher M.A.; Deering, Daryle; Dunn, Alistair; Berks, John; Nixon, Lee; Cape, Gavin
Abstract : Abstract: Despite the high rate of co-occurrence of major depression and alcohol dependence, the role of pharmacotherapy in their treatment remains unclear. In the new era of naltrexone for alcohol dependence, it is notable that only 1 study to date has examined the efficacy of antidepressant medication prescribed concurrently with naltrexone. We aimed to determine whether combining naltrexone with citalopram produced better treatment outcomes than naltrexone alone in patients with co-occurring alcohol dependence and depression, and to investigate whether either sex or depression type (independent or substance-induced depression) moderated treatment response. Participants were 138 depressed alcohol-dependent adults who were not required to be abstinent at the commencement of the trial. They were randomized to 12 weeks of citalopram or placebo, plus naltrexone and clinical case management. Treatment was well attended, and medications were reasonably well tolerated with high adherence rates. Substantial improvements in both mood and drinking occurred in both groups, with no significant differences between groups on any of the mood or drinking outcome measures, whether or not other variables were controlled for. No interaction effect was found for independent/substance-induced depression status, whereas there was a marginal effect found by sex, with greater improvement in 1 drinking outcome measure (percent days abstinent) in women taking citalopram. These findings suggest that citalopram is not a clinically useful addition to naltrexone and clinical case management in this treatment population. Independent/substance-induced depression status did not predict treatment response. Findings for sex were equivocal.